High-performance sodium ion battery positive electrode material as well as preparation method and application thereof
The conductivity of the sodium ion battery positive electrode material is solved by using the synergistic coupling effect of lithium titanium oxide compounds, aluminum compounds, two-dimensional graphene materials and thioacetamide on the sodium ion battery positive electrode material. The problem of low achieves high energy density and excellent electrochemical properties, and simplifies the production process.
Patent Information
- Application Number
- CN202411277882.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The low electronic conductivity of the cathode material of sodium ion battery leads to poor energy density and rate performance, and the existing carbon coating treatment methods are complex and difficult to achieve large-scale industrialization.
The phosphate-based positive electrode material is coated and modified by the synergistic coupling effect of hydrogen-containing lithium titanium oxide compounds, aluminum-containing compounds, two-dimensional graphene materials and thioacetamide to form a composite coating layer to improve sodium ion transport channels and conductivity.
The discharge specific capacity, cycle life and safety performance of the positive electrode material of sodium ion battery is significantly improved, high energy density and excellent electrochemical performance are achieved, and fully automatic continuous production is achieved through spray drying.
Smart Images

Figure BDA0005040777230000171 
Figure BDA0005040777230000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical power source material preparation, in particular to the technical field of sodium ion battery positive electrode material preparation, and relates to a high-performance sodium ion battery positive electrode material and a preparation method and use thereof. Background Art
[0002] Sodium-ion batteries (SIBs) are considered to be an important alternative to lithium-ion batteries (LIBs) due to their low cost due to the use of abundant and widely distributed sodium resources, and have good application prospects in the future energy storage field.
[0003] Based on strategic considerations of resource reserves and in-depth research and development of large-scale energy storage technology, replacing scarce and unevenly distributed lithium sources with low-cost, abundant and widely distributed sodium sources is of great value and far-reaching significance for achieving sustainable energy development. In addition, the sodium ions in sodium-ion batteries and the lithium ions in LIBs belong to the same family of alkali metal elements, have similar physical and chemical properties, their battery working principles are similar, and the industrial production systems of the two are highly compatible. SIBs can also be produced by making simple adjustments to the equipment and technology of the existing LIBs production system, which can greatly reduce costs. At the same time, compared with lithium-ion batteries, the negative electrode materials, current collectors and electrolytes adapted to sodium-ion batteries have obvious price advantages. Moreover, the internal resistance of SIBs is higher than that of LIBs, so there is less instantaneous heat generation and lower temperature rise in the case of short circuit. In addition, the thermal runaway temperature of SIBs is also higher than that of LIBs, making it more difficult to spontaneously ignite in high temperature environments. Finally, SIBs in a fully discharged state can be transported and stored more safely due to their low energy state and chemical stability. Therefore, SIBs are the preferred new battery system to replace LIBs, and they play a role in promoting the transformation and upgrading of the global energy structure.
[0004] However, SIBs also have obvious disadvantages. The radius of sodium ions (0.102nm) is about 1.3 times that of lithium ions (0.076nm). During the charge and discharge process, their migration rate is slower than that of lithium ions, which can easily cause uneven distribution of sodium ions in the electrode material, resulting in rapid degradation or collapse of the material structure. In addition, the atomic mass of sodium is 3.3 times that of lithium, resulting in the energy density of SIBs being only about 50% of that of lithium-ion batteries. Finally, the electrochemical potential of sodium is -2.713V, while the electrochemical potential of lithium is -3.040V, resulting in lower battery power and energy density of SIBs than LIBs.
[0005] As an important component in SIBs batteries, the cathode material plays a crucial role in the performance of SIBs batteries. Among them, the polyanionic cathode material Na3V2(PO4)3 (NVP) as a carrier for the reversible extraction / insertion of Na ions can be traced back to 1990. It is extended from the structure framework of the original sodium ion fast conductor (Na Super Ionic Conductor, NASICON) Na3Zr2PSi2O 12 The chemical formula of NASICON-type polyanionic cathode materials is Na x M(XO4)3 (M is V, Fe, Ti, Al, etc., X is P, S, Si, etc., 0 < x ≤ 4). NASICON-type materials based on PO4 3- are one of the most remarkable polyanionic compounds. With the in-depth research, researchers also found that by F - substituting PO4 3- its performance can be further improved.
[0006] Among the rich variety of polyanionic cathode materials, vanadium-based phosphate electrode materials have obvious advantages. NVP belongs to the R-3c space group and has a representative rhombic structure. The basic structure of NVP is VO6 octahedra and PO4 tetrahedra. The lantern-shaped [V2(PO4)3]3 - unit in the NVP structure is formed by three PO4 tetrahedra and two VO6 octahedra along the c-axis direction through a common top (oxygen atom). It is worth noting that there are a large number of hexagonal bottlenecks distributed in the NASICON structure, and these bottlenecks provide important diffusion interstitial sites for sodium ions. In addition, Na ions occupy two different sites: Na(1) (Wyckoff 6b site) and Na(2) (Wyckoff 18b site). In the structure framework of NVP, V is in the trivalent state and theoretically can accommodate three sodium ions. After research, one of them occupies Na(1), and the other two occupy Na(2). During charge and discharge, the Na ions located at Na(1) are fixed to maintain the framework, while the sodium ions located at Na(2) are removed for extraction / insertion between the positive and negative electrodes. However, the Na3V2(PO4)3 material has low electronic conductivity, resulting in low energy density and poor rate performance.
[0007] In order to solve the above problems, researchers are developing NVP with better performance through ion doping, coating and morphology control, so as to realize its large-scale application earlier. Carbon materials have excellent conductivity and are often used as conductive agents for Na3V2(PO4)3 materials to improve their conductivity. Some researchers have embedded carbon nanotubes into Na3V2(PO4)3 microspheres by spray drying (Nanoflake-constructed porous Na3V2(PO4)3 / C hierarchicalmicrospheres as a bicontinuous cathode for sodium-ion batteriesapplications.Nano Energy,2019,60:312-323). Carbon nanotubes can limit the growth of surface particles and form a three-dimensional carbon nanonetwork. This can not only significantly improve the conductivity of the material, but also the huge specific surface area increases the contact area between the electrode material and the electrolyte, which is beneficial to the transmission of active substances. Duan et al. (Na3V2(PO4)3@C core-shell nanocomposites for rechargeable sodium-ion batteries. Journal of Materials Chemistry A, 2014, 2(23): 8668-8675) used a hydrothermal method to obtain a sodium vanadium phosphate material (Na3V2(PO4)3 / C) uniformly wrapped with a carbon layer. The synthesized material has a layered porous structure with a stable framework. The experimental results show that compared with blank batteries, the Na3V2(PO4)3@C core-shell nanocomposites can effectively improve the rechargeable sodium-ion batteries. 4)3 / C as the positive electrode assembly of the battery has better cycle performance. Huang et al. (Ascorbic Acid-Assisted Synthesis of Mesoporous Sodium Vanadium Phosphate Nanoparticles with Highly sp 2 -Coordinated Carbon Coatings as Efficient Cathode Materials for Rechargeable Sodium-Ion Batteries.Chemistry-A European Journal, 2016, 22(30):10620-10626.) Using ascorbic acid as a reducing agent and carbon source, a highly sp 2Mesoporous Na3V2(PO4)3 nanoparticles with coordinated carbon coating (meso-Na3V2(PO4)3 / C). The sodium-ion full battery using meso-Na3V2(PO4)3 / C as the positive and negative electrode materials has a capacity retention rate of 92.2% and a coulombic efficiency of 99.5% after 100 cycles. Therefore, carbon-coated Na3V2(PO4)3 as a positive electrode material has a positive effect on the performance of sodium-ion batteries.
[0008] However, the above-mentioned carbon-coated Na3V2(PO4)3 still does not fundamentally solve the problem of low energy density and poor rate performance of sodium vanadium phosphate in sodium ion batteries due to low electronic conductivity. Moreover, the existing carbon coating treatment method is too complicated and time-consuming to achieve large-scale industrialization. Summary of the invention
[0009] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a high-performance sodium ion battery positive electrode material and its preparation method and use. The sodium ion battery positive electrode material of the present invention has high discharge specific capacity, excellent cycle life, high rate discharge and safety performance.
[0010] The sodium ion battery positive electrode material of the present invention has a higher discharge specific capacity and can therefore improve the energy density of the battery.
[0011] In the present invention, the "high performance" in the "high performance sodium ion battery positive electrode material" means that the battery made of the positive electrode material has a first discharge specific capacity of more than 112 mAh / g at a rate of 0.5C, a first coulombic efficiency of more than 96%, and a capacity retention rate of more than 94.2% after 150 cycles.
[0012] To achieve the above object, the present invention adopts the following technical solutions:
[0013] In a first aspect, the present invention provides a sodium ion battery positive electrode material, which includes a phosphate-based positive electrode active material and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide.
[0014] The present invention uses the synergistic coupling effect of hydrogen-containing lithium titanium oxide compounds and aluminum-containing compounds (such as AlF3 and / or Al2O3), two-dimensional graphene materials and thioacetamide to coat and modify the phosphate-based sodium ion battery positive electrode material, which can provide more sodium ion transmission channels, greatly improve the electronic conductivity and sodium ion transmission performance of the phosphate-based positive electrode material, and the sodium ion battery positive electrode material has a higher discharge specific capacity, excellent cycle life, high-rate discharge and safety performance. Compared with traditional coating materials, the introduction of sulfur elements in the coating layer through thioacetamide can expand the ion diffusion channel and reduce the charge transfer resistance, and can accelerate the ion migration rate; the addition of two-dimensional graphene materials can enable the sodium ion battery positive electrode material to obtain a higher sodium ion diffusion coefficient, the lowest impedance and the most excellent electrochemical performance; hydrogen-containing titanium oxide (such as H) itself has a high capacity x Ti y O z , where 0<x≤2, 0<y≤3, 0<z≤7) can improve the ionic conductivity of phosphate-based positive electrode materials, thereby greatly improving their discharge specific capacity and cycle stability; the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound can coat the surface of the phosphate-based positive electrode active material, which can reduce the contact between the surface active material and the air and inhibit the Na + The spontaneous extraction of ions improves the structural stability of the cathode material surface and inhibits the side reactions at the electrode-electrolyte interface, thereby improving the comprehensive electrochemical performance of the cathode material for sodium ion batteries.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] Preferably, the phosphate-based positive electrode active material is sodium vanadium phosphate or M-doped sodium vanadium phosphate, and the chemical formula of the phosphate-based positive electrode active material is Na3V 2-2x M x (PO4)3, wherein M is any one of Fe, Ti and Al or a combination of at least two, 0≤x≤0.5, and x can be, for example, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5. When x is 0, the phosphate-based positive electrode active material is sodium vanadium phosphate; when x is not 0, the phosphate-based positive electrode active material is M-doped sodium vanadium phosphate. Preferably, the hydrogen-containing lithium titanium oxide compound is a compound composed of four elements of Li, H, Ti and O in any proportion, including hydrogen-containing titanium oxide.
[0017] Preferably, the hydrogen-containing lithium titanium oxide compound is: Li4Ti5O12 , TiO2 and H x Ti y O z The compound preferably contains Li4Ti5O in any proportion in the phase structure. 12 and H2Ti3O7·(H2O·3TiO2), wherein 0<x≤4, 0<y≤3, 0<z≤7. Exemplarily, x can be, for example, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3, 3.4, 3.7 or 4, etc.; y can be, for example, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.5 or 3, etc.; z can be, for example, 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5 or 7, etc.
[0018] Preferably, the hydrogen-containing lithium titanium oxide compound is: Li 1.81 H 0.19 Ti2O5·aH2O, where a>0.
[0019] Preferably, the aluminum-containing compound comprises AlF3 and / or Al2O3.
[0020] Preferably, the two-dimensional graphene material includes reduced graphene oxide and / or graphene oxide.
[0021] As a preferred technical solution of the sodium ion battery positive electrode material of the present invention, based on the total mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 0.1-6wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt% or 6wt%, etc.
[0022] Preferably, based on the total mass of the sodium ion battery positive electrode material as 100%, the mass percentage of the two-dimensional graphene material is 0.1-5wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc.
[0023] Preferably, based on the total mass of the sodium ion battery positive electrode material as 100%, the mass percentage of the thioacetamide is 0.1-3wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, etc.
[0024] Preferably, the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is (6.5-9.5): (0.5-3.5), wherein the selection range of the hydrogen-containing lithium titanium oxide compound is "6.5-9.5", for example, it can be 6.5, 6.6, 6.8, 7, 7.3, 7.5, 7.8, 8, 8.5, 9 or 9.5, etc.; the selection range of the aluminum-containing compound is "0.5-3.5", for example, it can be 0.5, 0.8, 1, 1.3, 1.6, 2, 2.5, 3 or 3.5, etc.
[0025] In a second aspect, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described in the first aspect, the preparation method comprising the following steps:
[0026] (1) dispersing a surfactant in a solvent to obtain a solution A;
[0027] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1) to obtain a solution B;
[0028] (3) adding a phosphate-based positive electrode active material precursor and a sodium salt to the solution B obtained in step (2), and sand-milling to obtain a slurry C;
[0029] (4) The slurry C obtained in step (3) is spray-dried and heat-treated under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
[0030] In the method of the present invention, the surface of graphene oxide carries oxygen-containing functional groups, which is conducive to combining with other materials. At the same time, after heat treatment, the graphene oxide can be partially reduced to obtain reduced graphene oxide.
[0031] The present invention utilizes a spray drying method to ensure that the material has a uniform morphology, and after heat treatment, a uniform coating layer is formed in situ on the surface of the phosphate-based positive electrode material, which can form micropores with an appropriate content, thereby facilitating the acquisition of a sodium ion battery positive electrode material with high energy density and high electrochemical performance, and having high discharge specific capacity and first coulomb efficiency, and good cycle stability.
[0032] Moreover, the spray drying method can realize fully automatic continuous production, and has the advantages of large production capacity, high product quality and easy expansion.
[0033] As a preferred technical solution of the preparation method of the present invention, the surfactant in step (1) includes any one of F127, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate, or a mixture of at least two of them. Among them, F127 is a non-ionic surfactant composed of a polyoxyethylene-polyoxypropylene-polyoxyethylene (PEO-PPO-PEO) triblock copolymer.
[0034] Preferably, the solvent in step (1) comprises any one or a combination of at least two of water, isopropanol, ethylene glycol, acetone, tetrahydrofuran, ether, benzene, toluene or dimethylformamide, preferably any one or a combination of at least two of deionized water, isopropanol, ethylene glycol or acetone.
[0035] The present invention does not specifically limit the type of water, and it can be, for example, deionized water or ultrapure water.
[0036] As a preferred technical solution of the preparation method of the present invention, in step (2), after adding the hydrogen-containing lithium titanium oxide compound, the aluminum-containing compound, graphene oxide and thioacetamide, stir well and perform ultrasonic treatment.
[0037] Preferably, the temperature of the ultrasonic treatment is 50°C-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0038] Preferably, the power of the ultrasonic treatment is 80W-500W, for example, it can be 80W, 100W, 150W, 170W, 200W, 225W, 240W, 260W, 285W, 300W, 350W, 400W, 450W or 500W, etc.
[0039] Preferably, the ultrasonic treatment time is 0.5 h-3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.
[0040] As a preferred technical solution of the preparation method of the present invention, the phosphate-based positive electrode active material precursor in step (3) is M-doped vanadium phosphate.
[0041] Preferably, the sodium salt in step (3) comprises any one of sodium alginate, sodium carbonate, sodium vanadate, sodium acetate, sodium acetate trihydrate, sodium chloride, sodium bicarbonate, sodium phosphate, sodium nitrate, sodium phosphite, sodium sulfite, sodium formate, sodium propionate, sodium acrylate, sodium benzoate, sodium hypochlorite, sodium chlorate, sodium pyrovanadate, sodium dihydrogen phosphate, sodium perchlorate, sodium pyrophosphate, sodium thiosulfate, sodium persulfate, sodium silicate, sodium bromate, sodium bromide, sodium iodide and sodium dodecylbenzene sulfonate, preferably any one of sodium alginate, sodium carbonate, sodium dihydrogen phosphate, sodium vanadate, sodium acetate, sodium acetate trihydrate, sodium bicarbonate, sodium phosphate, sodium nitrate, sodium phosphite, sodium sulfite, sodium formate, sodium propionate, sodium acrylate, sodium benzoate, sodium hypochlorite, sodium chlorate, sodium pyrovanadate, sodium pyrophosphate, sodium thiosulfate, sodium persulfate and sodium bromate.
[0042] Preferably, the particle size of the slurry C obtained by sand grinding in step (3) is 100nm-2000nm, for example, it can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm or 2000nm, etc., preferably 150nm-1000nm, more preferably 200nm-800nm, and more preferably 250nm-600nm.
[0043] As a preferred technical solution of the preparation method of the present invention, the inlet temperature of the spray drying in step (4) is 150°C-280°C, for example, it can be 150°C, 160°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C or 280°C; the outlet temperature is 70°C-100°C, for example, it can be 70°C, 75°C, 80°C, 85°C, 90°C or 100°C.
[0044] Preferably, the gas in the inert atmosphere in step (4) includes any one or a combination of at least two of nitrogen, helium, neon, argon, krypton, xenon or radon, preferably nitrogen and / or argon.
[0045] Preferably, the temperature of the heat treatment in step (4) is 400°C-800°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc., preferably 500-600°C.
[0046] Preferably, the constant temperature time of the heat treatment in step (4) is 1 h to 24 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, 13 h, 15 h, 16 h, 18 h, 20 h, 22 h or 24 h, etc., preferably 4 h to 18 h.
[0047] Preferably, during the heat treatment in step (4), the rate of heating to the heat treatment temperature is 1°C / min-20°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 17°C / min, 18°C / min or 20°C / min, preferably 3°C / min-15°C / min, and more preferably 5°C / min-10°C / min.
[0048] Preferably, the method further comprises the steps of cooling and crushing and classifying after the heat treatment in step (4) is completed.
[0049] As a preferred technical solution of the preparation method of the present invention, (1) dispersing a surfactant in a solvent to obtain a solution A;
[0050] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring well, and ultrasonicating at 50-80° C. for 0.5 h-3 h to obtain a solution B;
[0051] Wherein, the aluminum-containing compound is AlF3 and / or Al2O3;
[0052] (3) adding the phosphate-based positive electrode active material precursor to the solution B obtained in step (2), and sand-grinding the solution to a particle size of 100 nm to 2000 nm to obtain slurry C;
[0053] (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 150° C.-280° C., and the outlet temperature is 70° C.-100° C.; and then heat-treated at 400° C.-800° C. for 1 h-24 h under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
[0054] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the first aspect.
[0055] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The present invention uses the synergistic coupling effect of hydrogen-containing lithium titanium oxide compounds and aluminum-containing compounds (such as AlF3 and / or Al2O3), two-dimensional graphene materials and thioacetamide to coat and modify the phosphate-based sodium ion battery positive electrode material, thereby providing more sodium ion transmission channels and greatly improving the electronic conductivity and sodium ion transmission performance of the phosphate-based positive electrode material. The sodium ion battery positive electrode material has a higher discharge specific capacity, excellent cycle life, high rate discharge and safety performance.
[0058] (2) The present invention utilizes a spray drying method to ensure that the material has a uniform morphology. After heat treatment, a uniform coating layer is formed in situ on the surface of the phosphate-based positive electrode material, and micropores of appropriate content can be formed, thereby facilitating the acquisition of a sodium ion battery positive electrode material with high energy density and high electrochemical performance, with high discharge specific capacity and first coulomb efficiency, and good cycle stability. Moreover, the spray drying method can realize fully automatic continuous production, and has the advantages of large production capacity, high product quality, and easy expansion. DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0060] Example 1
[0061] The present embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3V2(PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound includes Li4Ti5O 12 , TiO2 and H2TiO3, the aluminum-containing compound is AlF3, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 7:1.
[0062] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 3wt%, the mass percentage of the two-dimensional graphene material is 1wt%, and the mass percentage of thioacetamide is 1wt%.
[0063] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0064] (1) dissolving hexadecyltrimethylammonium bromide in isopropanol to obtain solution A;
[0065] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and performing ultrasonic treatment (temperature of 60° C., power of 300 W, time of 2 h) to obtain a solution B;
[0066] (3) adding sodium vanadium phosphate precursor and sodium alginate to the solution B obtained in step (2) according to the stoichiometric ratio of Na3V2(PO4)3, and grinding to a particle size of 250 nm to obtain slurry C;
[0067] (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 150° C. and the outlet temperature is 70° C.; then, the slurry is heat-treated in a nitrogen atmosphere (heated to 700° C. at a rate of 10° C. / min and kept at a constant temperature for 10 h) to obtain a positive electrode material for a sodium ion battery.
[0068] Example 2
[0069] This embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3VFe 0.5 (PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound is Li 1.81 H 0.19 Ti2O5·H2O, the aluminum-containing compound is a mixture of AlF3 and Al2O3, the mass ratio of AlF3 to Al2O3 is 1:1, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 8:2.
[0070] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 5.5wt%, the mass percentage of the two-dimensional graphene material is 3wt%, and the mass percentage of thioacetamide is 0.5wt%.
[0071] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0072] (1) dissolving sodium dodecylbenzene sulfonate in water to obtain solution A;
[0073] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and performing ultrasonic treatment (temperature of 50° C., power of 500 W, time of 1 h) to obtain a solution B;
[0074] (3) According to the stoichiometric ratio of Na3VFe 0.5 (PO4)3 add sodium vanadium phosphate precursor and sodium acetate trihydrate to the solution B obtained in step (2), and grind to a particle size of 600 nm to obtain slurry C;
[0075] (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 280° C. and the outlet temperature is 100° C.; then, the slurry is heat-treated in an argon atmosphere (the temperature is raised to 600° C. at a rate of 10° C. / min and kept constant for 6 hours) to obtain a positive electrode material for a sodium ion battery.
[0076] Example 3
[0077] This embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3VTi 0.25 Fe 0.25 (PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound includes Li4Ti5O 12 , TiO2 and H4TiO3, the aluminum-containing compound is Al2O3, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 9:3.
[0078] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 1wt%, the mass percentage of the two-dimensional graphene material is 0.5wt%, and the mass percentage of thioacetamide is 2wt%.
[0079] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0080] (1) dissolving hydroxyethyl cellulose in water to obtain solution A;
[0081] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and performing ultrasonic treatment (temperature of 80° C., power of 100 W, time of 3 h) to obtain a solution B;
[0082] (3) According to the stoichiometric ratio of Na3VTi 0.25 Fe 0.25 (PO4)3 add sodium vanadium phosphate precursor and sodium pyrophosphate to the solution B obtained in step (2), and grind to a particle size of 1000 nm to obtain slurry C;
[0083] (4) The slurry C obtained in step (3) was spray dried, wherein the inlet temperature of the spray drying was 180° C. and the outlet temperature was 80° C.; and then heat treated in a helium atmosphere (heated to 500° C. at a rate of 7° C. / min for 18 h to obtain a positive electrode material for a sodium ion battery.
[0084] Example 4
[0085] This embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3VAl 0.5 (PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound is Li 1.81 H 0.19 Ti2O5·3H2O, the aluminum-containing compound is a mixture of AlF3 and Al2O3, the mass ratio of AlF3 to Al2O3 is 3:1, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 6.5:2.5.
[0086] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 6wt%, the mass percentage of the two-dimensional graphene material is 5wt%, and the mass percentage of thioacetamide is 3wt%.
[0087] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0088] (1) Dissolve F127 in water to obtain solution A;
[0089] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and ultrasonically treating (temperature: 70° C., power: 200 W, time: 0.5 h) to obtain a solution B;
[0090] (3) According to the stoichiometric ratio of Na3VAl 0.5 (PO4)3 add sodium vanadium phosphate precursor and sodium carbonate to the solution B obtained in step (2), and grind to a particle size of 150 nm to obtain slurry C;
[0091] (4) The slurry C obtained in step (3) was spray-dried, wherein the inlet temperature of the spray-drying was 200° C. and the outlet temperature was 90° C.; and then heat-treated in a neon atmosphere (heated to 800° C. at a rate of 10° C. / min for 4 h to obtain a positive electrode material for a sodium ion battery.
[0092] Example 5
[0093] This embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3V 1.2 Ti 0.1 Al 0.1 Fe 0.2 (PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound includes Li4Ti5O 12 , TiO2 and H2Ti2O5, the aluminum-containing compound is AlF3, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 7:0.5.
[0094] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 2wt%, the mass percentage of the two-dimensional graphene material is 2wt%, and the mass percentage of thioacetamide is 0.5wt%.
[0095] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0096] (1) dissolving hexadecyltrimethylammonium chloride in ethanol to obtain solution A;
[0097] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and ultrasonically treating (temperature of 55° C., power of 400 W, time of 2.5 h) to obtain a solution B;
[0098] (3) According to the stoichiometric ratio of Na3V 1.2 Ti 0.1 Al 0.1 Fe 0.2 (PO4)3 add sodium vanadium phosphate precursor and sodium propionate to the solution B obtained in step (2), and grind to a particle size of 2000 nm to obtain slurry C;
[0099] (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 220° C. and the outlet temperature is 95° C.; then, the slurry is heat-treated in a nitrogen atmosphere (the temperature is raised to 750° C. at a rate of 10° C. / min and kept at a constant temperature for 10 h) to obtain a positive electrode material for a sodium ion battery.
[0100] Example 6
[0101] This embodiment provides a sodium ion battery positive electrode material, including a phosphate-based positive electrode active material (Na3V 1.6 Ti 0.2 (PO4)3) and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer includes a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide, wherein the two-dimensional graphene material includes reduced graphene oxide and graphene oxide, and the hydrogen-containing lithium titanium oxide compound is Li 1.81 H 0.19 Ti2O5·3H2O, the aluminum-containing compound is a mixture of AlF3 and Al2O3, the mass ratio of AlF3 to Al2O3 is 1:4, and the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 8:3.5.
[0102] Taking the mass of the sodium ion battery positive electrode material as 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 0.1wt%, the mass percentage of the two-dimensional graphene material is 0.5wt%, and the mass percentage of thioacetamide is 3wt%.
[0103] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps:
[0104] (1) dissolving hexadecyltrimethylammonium bromide in isopropanol to obtain solution A;
[0105] (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring and ultrasonically treating (temperature: 75° C., power: 350 W, time: 2.5 h) to obtain a solution B;
[0106] (3) According to the stoichiometric ratio of Na3V 1.6 Ti 0.2 (PO4)3 add sodium vanadium phosphate precursor and sodium alginate to the solution B obtained in step (2), and grind to a particle size of 120 nm to obtain slurry C;
[0107] (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 190° C. and the outlet temperature is 85° C.; then, the slurry is heat-treated in an argon atmosphere (heating to 650° C. at a rate of 10° C. / min and kept at a constant temperature for 7 h) to obtain a positive electrode material for a sodium ion battery.
[0108] Example 7
[0109] The difference between this embodiment and embodiment 1 is that the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 1:1.
[0110] Example 8
[0111] The difference between this embodiment and embodiment 1 is that the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is 20:1.
[0112] Comparative Example 1
[0113] The difference between this comparative example and Example 1 is that no hydrogen-containing lithium titanium oxide compound is added during the preparation of the positive electrode material, and other conditions are exactly the same as those in Example 1.
[0114] Comparative Example 2
[0115] The difference between this comparative example and Example 1 is that graphene oxide is not added during the preparation of the first coating, and other conditions are exactly the same as those in Example 1.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is that the aluminum-containing compound AlF3 is not added during the preparation of the positive electrode material, and the other conditions are exactly the same as those in Example 1.
[0118] Comparative Example 4
[0119] The difference between this comparative example and Example 1 is that thioacetamide is not added during the preparation of the positive electrode material, and other conditions are exactly the same as those in Example 1.
[0120] Battery assembly and performance testing:
[0121] The positive electrode materials of Examples 1-8 and Comparative Examples 1-4 are used to prepare positive electrode membranes. The preparation method is as follows: the synthesized positive electrode material, acetylene black and polyvinylidene fluoride are fully ground and mixed in a mass ratio of 80:10:10 in an N-methylpyrrolidone (NMP) solution. The prepared slurry is evenly coated on the surface of the carbon foil with a scraper, dried in a 70°C forced air oven for 4 hours, and then transferred to a 100°C vacuum drying oven for drying for 10 hours. The dried electrode sheet is cut into discs with a diameter of 10 mm for standby use, wherein the loading amount of the active material is 1.0 to 2.0 mg / cm 2 .
[0122] The metal sodium sheet was used as the counter electrode, GF / D was used as the separator, the electrolyte composition was: 1 mol / L NaClO4, a mixture of EC, DMC and EMC was used as the solvent, wherein EC: DMC: EMC (volume ratio) was 1:1:1, 5% fluoroethylene carbonate was added to the electrolyte, and the H2O and O2 contents were both less than 0.1 ppm (1 ppm = 10 -6 ) were assembled into CR2032 button cells in an argon atmosphere glove box. After the button cells were left to stand for 12 h, electrochemical tests were performed.
[0123] The electrochemical performance test was carried out on an American Arbin machine. The battery voltage test range was 2.0V to 4.3V. The first discharge specific capacity, first coulomb efficiency and capacity retention rate after 150 cycles of the button battery were tested at a rate of 0.5C (see Table 1 for the results).
[0124] Table 1
[0125]
[0126]
[0127] As can be seen from Table 1, the present invention adopts the synergistic coupling effect of hydrogen-containing lithium titanium oxide compounds and aluminum-containing compounds (such as AlF3 and / or Al2O3), two-dimensional graphene materials and thioacetamide to coat and modify the phosphate-based sodium ion battery positive electrode material, which can provide more sodium ion transmission channels and greatly improve the electronic conductivity and sodium ion transmission performance of the phosphate-based positive electrode material. The sodium ion battery positive electrode material has a higher discharge specific capacity, excellent cycle life, high rate discharge and safety performance.
[0128] By comparing Examples 1-6 with Examples 7-8, it can be seen that the mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is controlled within the range of (6.5-9.5):(0.5-3.5), which is beneficial to the improvement of electrochemical performance.
[0129] Compared with Example 1, Comparative Example 1 does not add hydrogen-containing lithium titanium oxide compounds during the preparation of the positive electrode material, resulting in reduced conductivity, and significantly reduced discharge capacity and cycle stability of the positive electrode material.
[0130] Compared with Example 1, in Comparative Example 2, graphene oxide is not added during the preparation of the positive electrode material, so that the electronic conductivity of the sodium vanadium phosphate positive electrode material is worse than that of Example 1, and the discharge specific capacity is only 95.3 mAh / g, which is lower than 117.2 mAh / g of Example 1. The capacity retention rate after 150 cycles is greatly reduced from 95.2% of Example 1 to 79.5%, but its coulombic efficiency is not greatly affected.
[0131] Compared with Example 1, in Comparative Example 3, no aluminum-containing compound is added during the preparation of the positive electrode material, which reduces the specific capacity, the first coulombic efficiency and the capacity retention rate after 150 cycles of the sodium vanadium phosphate positive electrode material to a certain extent.
[0132] Compared with Example 1, Comparative Example 4 does not add thioacetamide during the preparation of the positive electrode material, which results in the inability to effectively expand the ion diffusion channel during the charge and discharge process, the inability to better reduce the charge transfer resistance, and the inability to accelerate the ion migration rate. This leads to a decrease in the first discharge specific capacity, the first coulomb efficiency, and the capacity retention rate after 150 cycles of the positive electrode material.
[0133] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material comprises a phosphate-based positive electrode active material and a composite coating layer coated on the surface of the phosphate-based positive electrode active material, wherein the composite coating layer comprises a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, a two-dimensional graphene material and thioacetamide.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The phosphate-based positive electrode active material is sodium vanadium phosphate or M-doped sodium vanadium phosphate, and the chemical formula of the phosphate-based positive electrode active material is Na3V 2-2x M x (PO4)3, wherein M is any one of Fe, Ti and Al or a combination of at least two of them, and 0≤x≤0.5; Preferably, the hydrogen-containing lithium titanium oxide compound is a compound composed of four elements, Li, H, Ti and O, in any proportion, including hydrogen-containing titanium oxide; Preferably, the hydrogen-containing lithium titanium oxide compound is: Li4Ti5O 12 , TiO2 and H x Ti y O z The compound preferably contains Li4Ti5O in any proportion in the phase structure. 12 and H2Ti3O7·(H2O·3TiO2), wherein 0<x≤4, 0<y≤3, 0<z≤7; Preferably, the hydrogen-containing lithium titanium oxide compound is: Li 1.81 H 0.19 Ti2O5·aH2O, where a>0; Preferably, the aluminum-containing compound comprises AlF3 and / or Al2O3; Preferably, the two-dimensional graphene material includes reduced graphene oxide and / or graphene oxide.
3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that Based on the total mass of the sodium ion battery positive electrode material being 100%, the total mass percentage of the hydrogen-containing lithium titanium oxide compound and the aluminum-containing compound is 0.1 to 6 wt %; Preferably, based on the total mass of the sodium ion battery positive electrode material being 100%, the mass percentage of the two-dimensional graphene material is 0.1 to 5 wt%; Preferably, based on the total mass of the sodium ion battery positive electrode material being 100%, the mass percentage of the thioacetamide is 0.1 to 3 wt %.
4. The sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that The mass ratio of the hydrogen-containing lithium titanium oxide compound to the aluminum-containing compound is (6.5-9.5):(0.5-3.5).
5. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) dispersing a surfactant in a solvent to obtain a solution A; (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1) to obtain a solution B; (3) adding a phosphate-based positive electrode active material precursor and a sodium salt to the solution B obtained in step (2), and sand-milling to obtain a slurry C; (4) The slurry C obtained in step (3) is spray-dried and heat-treated under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
6. The preparation method according to claim 5, characterized in that: The surfactant in step (1) comprises any one of F127, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate, or a mixture of at least two thereof; Preferably, the solvent in step (1) comprises any one or a combination of at least two of water, isopropanol, ethylene glycol, acetone, tetrahydrofuran, diethyl ether, benzene, toluene or dimethylformamide, preferably any one or a combination of at least two of deionized water, isopropanol, ethylene glycol or acetone; Preferably, in step (2), after adding the hydrogen-containing lithium titanium oxide compound, the aluminum-containing compound, graphene oxide and thioacetamide, the mixture is stirred evenly and subjected to ultrasonic treatment; Preferably, the temperature of the ultrasonic treatment is 50°C-80°C; Preferably, the power of the ultrasonic treatment is 80W-500W; Preferably, the ultrasonic treatment time is 0.5h-3h.
7. The preparation method according to claim 5 or 6, characterized in that: The phosphate-based positive electrode active material precursor in step (3) is vanadium phosphate doped with M; Preferably, the sodium salt in step (3) comprises any one of sodium alginate, sodium carbonate, sodium vanadate, sodium acetate, sodium acetate trihydrate, sodium chloride, sodium bicarbonate, sodium phosphate, sodium nitrate, sodium phosphite, sodium sulfite, sodium formate, sodium propionate, sodium acrylate, sodium benzoate, sodium hypochlorite, sodium chlorate, sodium pyrovanadate, sodium dihydrogen phosphate, sodium perchlorate, sodium pyrophosphate, sodium thiosulfate, sodium persulfate, sodium silicate, sodium bromate, sodium bromide, sodium iodide and sodium dodecylbenzene sulfonate, preferably any one of sodium alginate, sodium carbonate, sodium dihydrogen phosphate, sodium vanadate, sodium acetate, sodium acetate trihydrate, sodium bicarbonate, sodium phosphate, sodium nitrate, sodium phosphite, sodium sulfite, sodium formate, sodium propionate, sodium acrylate, sodium benzoate, sodium hypochlorite, sodium chlorate, sodium pyrovanadate, sodium pyrophosphate, sodium thiosulfate, sodium persulfate and sodium bromate. Preferably, the particle size of the slurry C obtained by sand grinding in step (3) is 100nm-2000nm, preferably 150nm-1000nm, more preferably 200nm-800nm, and more preferably 250nm-600nm.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The inlet temperature of the spray drying in step (4) is 150°C-280°C, and the outlet temperature is 70°C-100°C; Preferably, the gas in the inert atmosphere in step (4) comprises any one or a combination of at least two of nitrogen, helium, neon, argon, krypton, xenon or radon, preferably nitrogen and / or argon; Preferably, the temperature of the heat treatment in step (4) is 400°C-800°C, preferably 500-600°C; Preferably, the constant temperature time of the heat treatment in step (4) is 1h-24h, preferably 4h-18h; Preferably, during the heat treatment in step (4), the rate of heating to the heat treatment temperature is 1°C / min-20°C / min, preferably 3°C / min-15°C / min, and more preferably 5°C / min-10°C / min; Preferably, the method further comprises the steps of cooling and crushing and classifying after the heat treatment in step (4) is completed.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: (1) dispersing a surfactant in a solvent to obtain a solution A; (2) adding a hydrogen-containing lithium titanium oxide compound, an aluminum-containing compound, graphene oxide and thioacetamide to the solution A obtained in step (1), stirring well, and ultrasonicating at 50° C. to 80° C. for 0.5 h to 3 h to obtain a solution B; Wherein, the aluminum-containing compound is AlF3 and / or Al2O3; (3) adding the phosphate-based positive electrode active material precursor to the solution B obtained in step (2), and sand-grinding the solution to a particle size of 100 nm to 2000 nm to obtain slurry C; (4) The slurry C obtained in step (3) is spray-dried, wherein the inlet temperature of the spray-drying is 150° C.-280° C., and the outlet temperature is 70° C.-100° C.; and then heat-treated at 400° C.-800° C. for 1 h-24 h under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material according to any one of claims 1 to 4.
